Two new species of the genus Hessebius Verhoeff, 1941 from China (Lithobiomorpha, Lithobiidae) - Penghai Qiao; Wen Qin; Huiqin Ma; Jianping Su; Tongzuo Zhang (ZooKeys, 2018)
Two new species, Hessebius luquensis sp. n. and Hessebius ruoergaiensis sp. n., are described based on material from Qinghai-Tibet Plateau. A key to the Chinese species of Hessebius is presented. The partial mitochondrial cytochrome c oxidase subunit I (COI) barcoding gene was amplified and sequenced for nine individuals of both species and the dataset was used for molecular phylogenetic analysis and genetic distance determination.